Optimalisasi Profitabilitas Perusahaan Farmasi melalui Rasio Likuiditas pada PT. Kimia Farma Pekanbaru - Wati, Murna (Jurnal Daya Saing, 2015)
Abstract: One important factor to measure the liquidity of a company then used Carrent Variable Ratio of dividing current assets by current liabilities Quick ratio is current assets minus persidiaan divided by current liabilities and inventories to Turn Over ie sales divided by inventory, and to measure the profitability of a companies use Return on Assets (ROA) is net profit after tax in the total asset.Berdasarkan background above problem, then the problem can be formulated as follows whether likuididas conditions significantly affect the level of profitability at PT. Kimia Farma Pekanbaru.Tujuan of research to obtain empirical evidence about whether liquidity significantly affect the level of profitability at PT. Kimia Farma Pekanbau The next test is to compare the profitability value (significance F) and a = 0, 05. SPSS printout of the results shows the probability value of 0.005 which is smaller than 0.05. so Ho is rejected and Ha accepted. This means that variable liquidity conditions significantly affect the condition profitabilitas.Sedangkan when in partial test, print out computer (attached) shows the results of a data analyst and partial hypothesis testing that variable curent Ratio indicates the level of significance of 0.005 which means that small of a = 0.05, so ho rejected and Ha accepted this means the current ratio variable effect on the level of profitability at PT Kimia Farma. Keywords: Likwiditas dan Profitabilitas